2020
DOI: 10.1186/s12915-020-00923-z
|View full text |Cite
|
Sign up to set email alerts
|

An optimized base editor with efficient C-to-T base editing in zebrafish

Abstract: Background Zebrafish is a model organism widely used for the understanding of gene function, including the fundamental basis of human disease, enabled by the presence in its genome of a high number of orthologs to human genes. CRISPR/Cas9 and next-generation gene-editing techniques using cytidine deaminase fused with Cas9 nickase provide fast and efficient tools able to induce sequence-specific single base mutations in various organisms and have also been used to generate genetically modified zebrafish for mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 31 publications
1
11
2
Order By: Relevance
“…Another more recent study employed the ancBE4max variant in zebrafish with a slight difference of efficiency that might be due to the choice of the specific locus targeted, the synthesis of the sgRNA (homemade vs commercially synthetized) and the injection mode (yolk vs cell) ( Carrington et al, 2020 ). More recently, Zhao et al, 2020 have shown similar efficiencies as we obtained in our study. To expand the gene-editing possibilities in this animal model, we established in addition a new editor variant recognizing the NAA PAM.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Another more recent study employed the ancBE4max variant in zebrafish with a slight difference of efficiency that might be due to the choice of the specific locus targeted, the synthesis of the sgRNA (homemade vs commercially synthetized) and the injection mode (yolk vs cell) ( Carrington et al, 2020 ). More recently, Zhao et al, 2020 have shown similar efficiencies as we obtained in our study. To expand the gene-editing possibilities in this animal model, we established in addition a new editor variant recognizing the NAA PAM.…”
Section: Resultssupporting
confidence: 92%
“…Together our work provides a panel of examples whereby, using gene editing approaches, some of which we established here in zebrafish for the first time, it is now possible to manipulate endogenous signaling pathways, to generate models for human genetic disorders and to mimic precise cancer-associated mutations in zebrafish. While a recent study reported the use of ancBE4max in zebrafish (Zhao et al, 2020), in our work we provide a direct comparison of BE4-gam, ancBE4max and Spymac-ancBE4max. Our study highlights the power and the need for these approaches to increase the efficiency and the targeting flexibility in order to model pathological human mutations in zebrafish.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optimization of CRISPR/Cas9 technologies for zebrafish continues apace, with recent success in high‐efficiency targeted integration through homology‐directed repair using DNA or single‐stranded oligonucleotide templates (Prykhozhij et al, 2018; Wierson et al, 2020) or by direct base editing (see, for example, Rosello et al, 2021; Zhao, Shang, Ying, Cheng, & Zhou, 2020). Such approaches, as already exemplified by targeted disruption of the zebrafish Adgrg6 Ca 2+ ‐binding site (Leon et al, 2020), can be used to introduce specific human disease mutations into the zebrafish gene or to create a humanized Adgrg6 gene in zebrafish, which will provide a valuable resource for ADGRG6 disease modeling and drug validation.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…The Cytidine Base Editor (CBE) is composed of a Cas9-D10A nickase fused to a cytidine deaminase and converts C-to-T bases in a restricted window of 13 to 19 nucleotides (nt) upstream of the PAM sequence without generating DSBs 6,7,8 . In zebrafish, several CBE variants have been shown to work with different gene editing efficiencies 9,10,11,12 . In a previous study we tested several CBE variants and we were able to reach a C-to-T conversion efficacy of 91% in zebrafish, showing many applications from signaling pathway activation to human disease modeling 12 .…”
Section: Introductionmentioning
confidence: 99%